Continuity and Transformation of Ijtihad in Islamic Law: Reassessing the Closed Gate Thesis through Classical Legal Texts - Upi Sopiah Ahmad; Faisar Ananda Arfa; M. Iqbal Irham; Nurasiah (Jurnal Syariah dan Hukum Komparatif, 2026)
This study reassesses the “closed gate of ijtihād” (insidād bāb al-ijtihād) thesis in Islamic law through a historical-textual analysis of classical legal works produced between the seventh and ninth centuries AH. Classical Orientalist scholars, most notably Joseph Schacht and Noel J. Coulson, argued that ijtihād declined after the consolidation of the legal schools and was replaced by the dominance of taqlīd. In contrast, contemporary scholars such as Wael B. Hallaq contend that ijtihād persisted through epistemic and institutional transformations within the madhhab tradition. Employing qualitative library research and content analysis, this study examines the works of al-Nawawī, Ibn Taymiyyah, and Tāj al-Dīn al-Subkī within the frameworks of Islamic legal epistemology and Legal Change Theory. The findings reveal that ijtihād continued to function dynamically through three principal models: ijtihād fi al-madhhab, ijtihād mustaqil, and ijtihād maqāṣidī. These models demonstrate that juristic diversity was an integral feature of the epistemological structure of Islamic law rather than evidence of historical stagnation. Consequently, the “closed gate of ijtihād” thesis is better understood as a historiographical construct than a normative-epistemic reality. The study contributes to the reconstruction of contemporary Islamic legal theory through a framework of continuity-in-transformation and offers a critical reassessment of Orientalist narratives concerning the development of Islamic law.